A Call to Action: Developing Sustainable Capital Markets, Financing Energy Transitions, and Building Project Pipelines - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2025)
This report is set out in two parts. Part one of this report discusses selected areas of the Addis Ababa Action Agenda, a global policy framework to realign financial flows with sustainable development goals agreed in 2015, in Asia and Pacific. The selected areas include strengthening domestic public resources, Domestic and international private business and finance, debt and debt sustainability, and addressing systemic issues. Part two, co-authored with United Nations Framework Convention on Climate Change, Asian Development Bank, Climate Bonds Initiative and International Renewable Energy Agency, puts forward a coherent set of policy actions that are needed to be undertaken by policymakers and regulators to strengthen sustainable capital markets, finance the energy transition, and to strengthen project pipelines for the economic transitions required for climate action.